2007
DOI: 10.1111/j.1365-2222.2007.02873.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene D4‐induced, epithelial cell‐derived transforming growth factor β1 in human bronchial smooth muscle cell proliferation

Abstract: In conclusion, elevated expression of cys-LTs in asthmatic airways might contribute to BSMC hyperplasia and concomitant clinical features of asthma such as airway hyperresponsiveness via a paracrine loop involving TGF-beta1 production by airway epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Nevertheless, it is also reported that LTD 4 alone can not increase the growth of bronchial fibroblasts and smooth muscle cells, but potentiates the proliferation induced by epidermal growth factor (EGF) (30,31). This indicates that the effect of LTD 4 on cell proliferation relates to cell types and the interaction with other growth factors (32). Taking together, we consider that the angiogenic effect of LTD 4 is incomplete; it facilitates migration, while growth factors / cytokines (like VEGF and EGF) or complex interactions may regulate proliferation of endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, it is also reported that LTD 4 alone can not increase the growth of bronchial fibroblasts and smooth muscle cells, but potentiates the proliferation induced by epidermal growth factor (EGF) (30,31). This indicates that the effect of LTD 4 on cell proliferation relates to cell types and the interaction with other growth factors (32). Taking together, we consider that the angiogenic effect of LTD 4 is incomplete; it facilitates migration, while growth factors / cytokines (like VEGF and EGF) or complex interactions may regulate proliferation of endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…Mf in the M2 spectrum confer fibrosis and remodeling (22,41), and another effect of Cys-LTs is induction of TGFb, furin, and VEGF, leading to tissue remodeling in chronic asthma (44)(45)(46). It is tempting to speculate that the M-CSF-derived Mfs studied here, with high capacity for LTC 4 biosynthesis, may resemble pulmonary M2 cells active in allergic lung inflammation (22).…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that the increased cysLT production in AECs induces the secretion of TGF-b1. Leukotriene D 4 has been shown to induce TGF-b1 production in human bronchial epithelial cells (43). The production of cysLTs by latently infected AECs is likely to promote fibrosis via effects on mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%